Advanced framework for highly secure and cloud‐based storage of colour images. Issue 13 (2nd October 2020) - Chidambaram, Nithya; Raj, Pethuru; Thenmozhi, Karruppuswamy; Amirtharajan, Rengarajan
Abstract : The evergrowing virtualised information technology infrastructure is powered by cloud‐centric technology around the world. Cloud‐based multimedia storage has become an essential aspect for users and business behemoths. However, as per a survey of Norton, around 3800 breaches have been publicly disclosed with 4.1 billion numbers of records exposed in 2019, which is a 54% rise when compared to 2018. So the data security is a widely quoted barrier for cloud storage. Ciphering the confidential images before transmission and subsequent storage in cloud database needs critical attention for techno‐specific applications. In image encryption, chaos‐based keys can do better confusion, but the diffusion process using XOR is vulnerable to chosen plain text attack. The proposed colour image encryption scheme innately uses Deoxyribo Nucleic Acid coding that blends well with chaotic cryptosystem for an efficient statistical shift. The ciphered images are stored in authenticated and authorised cloud storage facilities. The experimentation is carried out with the help of Amazon Web Services storage instances. The proposed image encryption scheme offers a strong resistance towards the brute force, occlusion, statistical and differential attacks and yields near‐zero correlation and good entropy.